Upper Gastrointestinal Symptoms and Climate Exchange in Indonesian Hajj Pilgrims: Community Based Study Islamic Year 1427 - Masdalina Pane; Chairul R Nasution; Murdani Abdullah (The Indonesian Society for Digestive Endoscopy, 2007)
Background: Upper gastrointestinal symptoms rank among the three most common diseases for Indonesian hajj pilgrims in last 4 years. The prevalence was 22-34% per hajj season. Most of the cases were dyspepsia syndrome and Gastro Esophageal Reflux Disease (GERD). The internal risk factor of Upper gastrointestinal symptoms is largely known, but not for external factor such as environment and climate. Aim: To examine the association between climate exchange and upper gastrointestinal symptoms Methods: Dynamic population of 204,941 Indonesian Hajj Pilgrims in Islamic year 1427 were included for this study. Multiphase screening in Indonesia found the prevalence of upper gastrointestinal symptoms was 3.32%. Prospective follow up for upper gastrointestinal symptom-based on community health services (flight group/kloter and maktab policlinic/polimaktab) and hospital base (Sub Balai Pengobatan Haji Indonesia, Balai Pengobatan Haji Indonesia [BPHI] and Saudi Arabia hospital) was conducted in Saudi Arabia. Results: The incidence rate of the upper gastrointestinal symptoms was 2.4 per mile (95% CI = 1.8 -3.1). There was no significant difference among male and female p = 0.279 (95% CI = 0.18- 5.3) and there was significant difference among work area (Daker) p = 0.001 (95% CI = 50.4-182.5). There was no significant correlation between upper gastrointestinal symptoms and temperature or humidity in 3 work area (p = 0.155) Mecca, Medina and Jeddah. Conclusion: There was no significant correlation between climate exchanges to the upper gastrointestinal symptoms. Keywords: upper gastrointestinal symptoms, Indonesian Hajj Pilgrims, dyspepsia, GERD